Protection of the Right to Freedom of Religion in Indonesia (Case Study: Destruction of the Ahmadiyah Mosque in Balai Harapan Village, Temunak District, Sintang District, West Kalimantan) (Journal of Creativity Student, 2021)
As in most modern law countries, the State of Indonesia has a regulation regarding guarantees for religious rights and freedoms. This is implied in the constitution of the State of Indonesia, namely the 1945 Constitution of the Republic of Indonesia, precisely in Article 28 E paragraph (1) which reads "Everyone is free to embrace religion and worship according to his religion, choose education and teaching, choose work, choose citizenship, choose a place to live in the territory of the country and leave it, and have the right to return.” Along with regulations related to religious freedom, the State also has a role in guaranteeing its people to be able to embrace their respective religions which has been stated in Article 29 Paragraph (2), namely "The State guarantees the independence of each resident to embrace their respective religions and to worship. according to his religion and belief." Although the guarantee of the right to freedom of religion has been regulated in the constitution of the Unitary State of the Republic of Indonesia, in its concretization there are still many obstacles and problems. Talking about the right to freedom of religion, there are interesting things to always talk about and it is hoped that there will be a solution in the future, namely related to acts of violence in the name of religion. Recently, the Indonesian people were shocked by the act of destroying the mosque belonging to the Ahmadiyah congregation by intolerance and radicalism, to be precise, on Friday, September 3, 2021, in Balai Harapan Village, Temunak District, Sintang Regency, West Kalimantan. Seeing the barbaric actions carried out by the intolerant, the government needs firmness in enforcing the law and mediating between the minority and the majority.